2017
DOI: 10.1002/jcp.25765
|View full text |Cite
|
Sign up to set email alerts
|

Current Status and Prospective Regarding the Therapeutic Potential of Natural Autoantibodies in Cancer Therapy

Abstract: The presence of natural auto-antibodies (NAbs) in normal range/activity in healthy individuals is essential for body to maintain hemostasis, which are directed to self and altered self-components, while abnormal activity of this system can be associated with several health related diseases. It has been shown that NAbs regulate immune system, and can be changed during the individual's life. In other word, the level and pattern of Nabs is among the main factors to define the state of the body, suggesting their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Natural autoantibodies are mainly produced by B-1 cells in the absence of external stimulation 16 , and have a series of physiological activities such as maintaining homeostasis of the immune system 17 , pathogen elimination 18 , regulating B cell development 19 and immune defense 20 . Because of an age-related reduction of natural autoantibodies, a decline of its ability to remove noxious molecules might be associated with the development and progression of several chronic illnesses commonly occurring in middle-age or older people such as neurodegeneration, type-2 diabetes, atherosclerosis and malignant diseases 21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural autoantibodies are mainly produced by B-1 cells in the absence of external stimulation 16 , and have a series of physiological activities such as maintaining homeostasis of the immune system 17 , pathogen elimination 18 , regulating B cell development 19 and immune defense 20 . Because of an age-related reduction of natural autoantibodies, a decline of its ability to remove noxious molecules might be associated with the development and progression of several chronic illnesses commonly occurring in middle-age or older people such as neurodegeneration, type-2 diabetes, atherosclerosis and malignant diseases 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Because of an age-related reduction of natural autoantibodies, a decline of its ability to remove noxious molecules might be associated with the development and progression of several chronic illnesses commonly occurring in middle-age or older people such as neurodegeneration, type-2 diabetes, atherosclerosis and malignant diseases 21 . Therefore, researchers have suggested that natural autoantibodies could be used as biomarkers for identification of immune-related conditions such as cancer 17 .…”
Section: Introductionmentioning
confidence: 99%
“…One of the limitations of this approach is that virus delivery strategy is not always successful at effectively delivering oncolytic viruses to tumors. Another limitation is that circulating antiviral antibodies can neutralize OVs and reduce their therapeutic potential of virotherapy . To overcome these limitations, several targeted strategies and armed therapeutic viruses have been designed and were successful in enhancing this approach .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the relationship between autoantibodies and tumors [ 1 ]. The anti-reticulin antibody (ARA)was first identified in 1971 and was used as a specific marker for gluten-sensitive enteropathy [ 2 3 ], playing a supportive role in the diagnosis of celiac disease.…”
mentioning
confidence: 99%
“…Natural autoantibodies regulate the immune system. Therefore, it is possible that various types of autoantibodies may be detected in conditions, in which homeostasis is disrupted, in cluding malignant tumors [ 1 ]. In addition, autoantibodies have been transiently detected in patients undergoing treatments such as interleukin therapy for malignant tumors [ 7 8 ].…”
mentioning
confidence: 99%